Association between sleep quality and MCI in older adult patients with multimorbidity - Yang, Ting; Zheng, Guoyan; Peng, Shuzhi (Frontiers in Public Health, 2025)
ObjectiveTo explore the relationship between sleep quality and mild cognitive impairment in older adult patients with multimorbidity.MethodsThe general data of older adult patients with chronic diseases were collected, and the sleep quality and mild cognitive impairment (MCI) of older adult patients with multimorbidity were investigated by questionnaire. Logistic regression model and restricted cubic spline (RCS) model were used to analyze the correlation between sleep quality and MCI in older adult patients with multimorbidity.ResultsThere are 902 valid samples in this study, of which 333 (36.9%) have MCI. The number of chronic diseases ranges from 2 to 6, and the number of types of medication ranges from 0 to 7. The score of PSQI is 2–18, with an average score of 11.13. MoCA score range is 7–30. The MoCA score of MCI patients is lower than that of Non-MCI patients. In all three models, PSQI score is significantly correlated with MCI. The results of the segmented regression analysis show that: the inflection point of MCI’s PSQI scoring relationship is 12. RCS result display: with the increase of PSQI score, the OR increases between PSQI score and MCI, when PSQI score reaches 12, OR is significantly higher than 1.ConclusionSleep quality is an important influencing factor of MCI, and there is a threshold effect in the above association. According to this correlation, health professionals can take measures to improve the sleep quality of older adult patients with multimorbidity to reduce the occurrence of MCI.